Financial Adaptation in The Digital Era: The Importance of Financial Literacy Education for The Community - Kiki Azakia; Billy Dewantara; Dwi Riana; Ulfah Muharramah; Yesita Astarina; Rizal Afif Abdullah Napitupulu; Andriansyah Bari; Dika Setiagraha (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This community engagement program aims to enhance financial literacy and adaptability among twelfth-grade students at SMK Ethika Palembang through an engaging and participatory educational approach. The methods employed include face-to-face sessions supported by educational videos, thematic games, and interactive discussions. The results reveal a significant improvement in students’ understanding of key financial concepts such as distinguishing needs from wants, the importance of saving, and basic financial planning. The program effectively fostered more responsible financial behavior and equipped students with the skills to navigate future economic challenges. These outcomes highlight the importance of integrating financial literacy into formal curricula, encouraging parental involvement, and utilizing digital tools to support sustainable financial education for youth.